Structural Equation Model of Factors Affecting Employee Learning at Day Insurance Company Based on Heutagogy Approach - Ghalandari , Hasan; Mohamaddavodi, Amirhossein; Jafari , Parivash (Management Strategies and Engineering Sciences, 2024)
The study aimed to investigate the factors influencing employee learning based on the heutagogy approach at Day Insurance Company. By focusing on individual, organizational, and environmental factors, the research sought to identify their contributions to self-determined learning in a workplace context. The study further aimed to validate a structural equation model of these factors and their relationships with employee learning outcomes, providing insights for fostering heutagogical practices in organizations. A quantitative survey-based research design was employed to collect data from employees of Day Insurance Company. A researcher-designed questionnaire was developed to assess factors influencing heutagogical learning, which included individual (e.g., motivation, job satisfaction), organizational (e.g., managerial support, feedback mechanisms), and environmental (e.g., socio-cultural factors) dimensions. The sample consisted of 230 employees, selected using the Cochran formula. Data were analyzed using SPSS for descriptive statistics and SmartPLS for structural equation modeling to evaluate the relationships among variables and the overall model fit. The results revealed that individual factors had the strongest influence on employee learning outcomes, with motivation and job satisfaction emerging as critical contributors. Organizational factors, such as managerial support, job expectations, and technological infrastructure, also significantly impacted learning outcomes, while environmental factors played a comparatively weaker role. The model demonstrated a strong fit (R² = 0.834), indicating that the identified factors accounted for 83.4% of the variance in employee learning outcomes. These findings highlight the importance of both individual agency and organizational support in implementing heutagogical learning practices. The study underscores the effectiveness of the heutagogy approach in fostering employee learning, with individual and organizational factors playing pivotal roles. Organizations should prioritize strategies that enhance motivation, provide supportive feedback, and invest in technological infrastructure to support self-determined learning. These findings contribute to the growing body of research on heutagogy and its practical applications in workplace learning.